Die Pflanzungen Britisch-Kameruns als Beispiel eines fortschrittlichen Wirtschaftskernes im tropischen Afrika - Rieht, Dietrich (ERDKUNDE, 1953)
The building up of an economic core which is based on geographical factors in the British-Cameroons has only been made possible by the use of migratory labour. In contrast to most other similar areas, the planters of the Cameroon Mountain have been able to train a stock of settled and contented labourers by means of a generous social policy which however in this case was supported by favourable circumstances. Subsequently migratory labour was employed only to meet peak requirements. In this way Cameroon planters have taken the lead in establishing a colonization which is productive and yet sound.